Analysis of Students' Sports Exercise Behavior and Health Education Strategy Using Visual Perception–Motion Recognition Algorithm - Chen, Minwei; Zhou, Yunzheng (Frontiers in Psychology, 2022)
This paper aims to explore the future development path of college Health Education and Health Education's impact on students' sports exercise. Specifically, Artificial Intelligence (AI) algorithm is combined with intelligent robotics technology to acquire and analyze students' sports exercise behaviors. As a result, a new development model is formulated for college Health Education. Firstly, it explores students' sports exercise and Health Education situation in Chinese higher institutions and uncovers the underlying problems. Then it puts forward corresponding modification suggestions. Secondly, the AI algorithm and the Kinect sensor-mounted intelligent robot capture the human skeleton features to obtain smooth skeleton joint points data. At the same time, a visual perception Human Motion Recognition (HMR) algorithm is established based on the Hidden Markov Model (HMM). Afterward, the proposed HMM-based HMR algorithm is used to recognize students' sports exercise motions by analyzing human motion skeleton images. The experimental outcomes suggest that the maximum reconstruction error of the HMR algorithm is 10mm, and the compression ratio is between 5-10; the HMR rate is more than 96%. Compared with similar algorithms, the proposed visual perception HMR algorithm depends less on the number of training samples. It can achieve a high recognition rate given only a relatively few samples. Therefore, the proposed (AI + intelligent robot)-enabled HMM-based HMR algorithm can effectively identify the behavior characteristics of students in sports exercise. This paper can provide a reference for exploring college students' Health Education development path.